Râvi olarak Amr B. Âs ve rivâyetleri - Çimen, Abdullah (My University, 2017)
Amr b. Âs İslâm tarihinde ve hadis tarihinde önemli bir yere sahiptir. İslâm’ın ilk dönemlerinde siyâsî olaylarda önemli rol oynamış, Hz. Peygamber’den de birçok hadis rivâyet etmiştir. Müslüman olmadan önce Hz. Peygamber’e karşı savaşmış, Müslüman olduktan sonra da İslâm’a çok büyük faydaları dokunmuştur. Suriye, Filistin ve Mısır’ın fethini gerçekleştiren kumandanlardan biridir. Özellikle siyâsî kişiliği sebebiyle tartışılmış, hakkında çok şey söylenmiş, haksız birtakım eleştirilere de maruz kalmıştır. Bu çalışmada onun bu yönü araştırılmış ve hakkında söylenenlerin doğru olmadığı ortaya çıkmıştır. Amr b. Âs bir râvi olarak Hz. Peygamber’den hadis de nakletmiştir. Naklettiği hadislerin hemen hemen hepsi genel ve güvenilir kaynaklarda yer almıştır. Yapılan araştırmalarda rivâyetlerinin ağırlıklı olarak sahih, râvilerinin de güvenilir olduğu ortaya çıkmıştır. Amr b. el-Âs, sahâbe, tenkit, hadis, râvi

Amr ibn al-Âs occupies a significant placein the history of Islamand hadith. He played a crucial role in the political eventsduring the early times of Islam and also narrated numerous hadiths from the Prophet. Despite having fought against the Prophet before becoming Muslim, he made great contributions to Islam after he embraced I slam. He was one of the commanders who conquered Syria, Palestine and Egypt. There have been many discussions and discourses on him regarding his political character and he is object to certain critics as well. In this study, this aspect of Amr ibn al-Âs is explored and it arouse that the things have been told about him are not actually true. As a companion, being a narrator of the hadiths from the Prophet, almost all of the hadiths he narrated are found within the reliable sources. As a result of the study, it came out that his narrations are mainly sound (sahih) and the narrators of the narrations are reliable. Amr b. al-Âs, companions, criticism, hadîs, transmitter
Keywords: Biyografi; Hadis; Hadisler; İslam; İslam dini; Rivayetler